2021
DOI: 10.1590/1678-7757-2020-0770
|View full text |Cite
|
Sign up to set email alerts
|

Fcγ receptors on aging neutrophils

Abstract: Fcγ receptors on aging neutrophilsObjective: Neutrophils are key effector cells of the innate immune system.They recognize antigens through membrane receptors, which are expressed during their maturation and activation. Neutrophils express FcγRII (CD32), FcγRIII (CD16), and FcγRI (CD64) after being activated by different factors such as cytokines and bacterial products. These receptors are involved with phagocytosis of IgG-opsonized microbes and enhance defense mechanisms.Based on that, our study seeks to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…Valziflocept is a recombinant soluble FcγIIb receptor that targets Fc and 10.3389/fnins.2022.994575 FcγR (Zuercher et al, 2019). FcγR has been reported as a potential therapeutic target for pain in autoimmune diseases (Bersellini Farinotti et al, 2019;Peyrin-Biroulet et al, 2019), and it was also crucial in aging neutrophils (Gasparoto et al, 2021). There is no doubt that Valziflocept may benefit patients with comorbidities of pain and aging to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Valziflocept is a recombinant soluble FcγIIb receptor that targets Fc and 10.3389/fnins.2022.994575 FcγR (Zuercher et al, 2019). FcγR has been reported as a potential therapeutic target for pain in autoimmune diseases (Bersellini Farinotti et al, 2019;Peyrin-Biroulet et al, 2019), and it was also crucial in aging neutrophils (Gasparoto et al, 2021). There is no doubt that Valziflocept may benefit patients with comorbidities of pain and aging to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…S7b ), while we observed significant downregulations of Cd16 and Cd32 (two genes that encode Fc Gamma Receptor IIIa (FCGR3A) and Fc Gamma Receptor IIa (FCGR2A), respectively and are known to be important for the activation of neutrophils) in the hEnSC group, which indicates that neutrophils generally remained inflammatory with some changes upon hEnSC transplantation. 61 These findings clearly demonstrated that the activation state of macrophages/Kupffer cells and the general hepatic immune micromilieu were skewed towards an anti-inflammatory state after hEnSC transplantation and that IFN signaling was significantly downregulated in liver macrophage populations. It would be interesting to interrogate whether or how hEnSCs or their derivatives were efferocytosed by macrophages/ Kupffer cells which might have a major effect on the latter.…”
Section: Discussionmentioning
confidence: 73%
“…Immunosenescence changes the phenotype neutrophils from the bloodstream as well as those entering the tissues. These modifications coupled with dysbiosis of the oral microbiota will promote DRCS [ 97 , 152 , 153 ]. DRCS neutrophils are not fully primed by the process of extravasion, but are more affected by the local inflammatory environment of the DRCS.…”
Section: Neutrophils and Denture-related Candida Stomatitismentioning
confidence: 99%